Pengembangan Media Pembelajaran Berbasis Aplikasi Codular Pada Materi Proses Penghelasan Metal Inert Gas (MIG) - Pudyatmoko, Kristanto; Sunardi, Sunardi; Wunarlan, Irwan; Yasser Arafat, Muhammad; Rahmad Machmoed, Buyung (Rifa'Institute, 2023)
The aim of this research is to develop learning media and determine the validity and practicality of learning media based on the Codular application in MIG welding subjects at vocational schools. This research uses the Research and development method with the 4D development model (Define, Design, Develop and Disseminate). This research was carried out at SMKN 3 Gorontalo with research subjects in class XI Welding Engineering Skills Competency. The data collection technique uses a questionnaire to assess validity, practicality and attractiveness. The data analysis technique in this research uses quantitative percentage data analysis. The results of the validation assessment by material experts were 95.3% in the very feasible category, the assessment by media experts was 89.2% in the very feasible category, the practicality assessment by users was 88.6% in the very feasible category and the attractiveness assessment was 88.4% with a very worthy category. Based on the results of the research and discussion, it can be concluded that codular-based learning media is very feasible, practical and interesting to use in learning MIG welding theory.